A Rare Case of Chronic Lymphoproliferative Disorder of NK Cells with an Unusual Expression of CD57. (28th October 2020) - Laharwani, H; Perrizo, K; Jain, S; Lam, J
Abstract: Introduction/Objective: Natural Killer cells (NK-cells) malignancies are extremely rare and the two NK-cell disorders involving the peripheral blood and bone marrow include chronic lymphoproliferative disorder of NK-cells (CLPDNK) and aggressive NK-cell leukemia (ANKL). ANKL is EBV associated with a prevalence in Asian adults and a fulminant clinical course leading to death within 2 months. Methods: A 76-year-old female with a history of iron deficiency anemia presented for evaluation of lymphocytosis (78 TH/mm) and negative EBV with extreme fatigue, weight loss, and worsening weakness from the past 8 months. Results: The peripheral and bone marrow aspirate showed an increase in granular lymphocytes with bland nuclei and abundant pale-staining cytoplasm containing fine to coarse azurophilic granules with no evidence of nuclear atypia. Flow cytometry demonstrated an atypical lymphocytic cell population comprising >50% of total marrow and peripheral blood lymphocytes demonstrating loss of CD56 and diminished CD7 expression. The analysis showed atypical lymphocytes with the following immunophenotype: CD2, CD8 (the majority, at least 75%), CD7 (dim), CD38, CD11c (subset) with no expression of CD3, CD5, CD4, CD56, or CD11c. Flow cytometry is important as it helps in the phenotypic detection of aberrancy. A broad panel of immunohistochemical stains revealed scattered positivity for CD3, CD4, CD7, CD8, TIA-1, granzyme, perforin, and tryptase and negative for CD56 and CD57. Our top differential with a similar clinical course included T-cell large granular lymphocytic leukemia which is characterized by a clonal proliferation of mature cytotoxic T cells and also has an indolent course. They show CD3 positivity by flow cytometry along with co-expression of NK cell-associated markers (CD16 and CD57), and variable expression of other pan T cell markers such as CD2, CD5, CD7. It is found incidentally in patients having cytopenias with a persistent increase in circulating mature NK-cells. Of note, the PET scan revealed splenomegaly with no other significant findings.The patient was started on steroids and is currently doing well. Conclusion: Thus, overall morphologic, immunophenotypic, and molecular results with negative expression of surface or cytoplasmic CD3 as well as the absence of TCR expression were most consistent with CLPD-NK with an unusual expression of CD57 expression detected in flow cytometry.